Microbial mechanisms mediate divergent ecosystem responses to nitrogen and phosphorus enrichment - Zehao Lv; Gangsheng Wang; Daifeng Xiang; Xiankai Lu; Mingkai Jiang; Donghai Wu; Qinggong Mao; Shuhao Zhou; Shanshan Qi; Zirui Mu; Yilei Zhong; Mianhai Zheng; et al. (Soil Biology and Biochemistry, 2026)

Salinity dynamics in a dryland large lake over the past 2 kyr and its driving forces - Muhammad Farqan; Lixiong Xiang; Wenjia Wang; Jiayu Deng; Xiaoyan Mu; Xin Liu; Ruiqi Min; Chong Huang; Mingjie Sun; Luciane Fontana; Xiaozhong Huang (Quaternary Science Reviews, 2026)

Deciphering mechanisms of environmental adaptation, antibiotic tolerance, and potential virulence traits of Pseudomonas baetica isolated from anthropogenic habitat - Mu-Qi Zhang; Yi-Cheng Wang; Ming-Ying Mao; Yin-Qiu Qin; Peng Yan; Hui-Min Fu; Yuan-Xiang Mao; Ji-Cheng Liu; You-Peng Chen; Meng-Jiao Gao (Journal of Environmental Chemical Engineering, 2026)

Extraction optimization, purification, and structural characterization of Yacon polysaccharide: An inhibitor against α-glucosidase/α-amylase - Zhen-Zhou Li; Zhe-Xuan Mu; Shao-Feng Li; Yi-Han Ding; Shadrack Vundi Benjamin; Ruo-Jia Zhu; Xiang-Yu Wang; Zhen-Yu Wang; Hua Zhang (Food Chemistry, 2026)

Simultaneous elimination of sulfonamides and antibiotic resistance genes via peroxymonosulfate activation by ligand-modulated iron sites on biochar: The critical role of interfacial EDTA complexation - Yifan Liu; Fengxia Yang; Xue Li; Zhikang Deng; Xi Chen; Minghui Xiang; Ran Zhao; Xiaoquan Mu; Yongzhen Ding; Junjie Wang; Zulin Zhang (Chemical Engineering Journal, 2026)

An eco-friendly integrated short-process of ffor low-grade nickel laterite ore utilization: Glycolic acid leaching kinetics and direct hydro-thermal synthesis of spinel NiFe2O4 anodes - Anlu Wei; Wenning Mu; Xiaolong Bi; Xiang Li; Xuefei Lei; Shaohua Luo (Process Safety and Environmental Protection, 2026)

Nonlinear microbial thresholds drive non-additive soil greenhouse gas responses to compound climate extremes - Zehao Lv; Gangsheng Wang; Daifeng Xiang; Shuhao Zhou; Wanyu Li; Shanshan Qi; Yajing Han; Zirui Mu; Yilei Zhong; Shuang Li; Yuhao Pan; Jiahe Liu (Agricultural and Forest Meteorology, 2026)

Recombinant bovine αs1-casein as an enhanced precursor for sleep-promoting peptides: A structural, peptidomic, and molecular docking study - Long Pan; Lin-Lin Ding; Meng-Jia Song; Xiang-Li Mu; Ai-Mei Liao; Yin-Chen Hou; Ji-Hong Huang; Guang-Hai Yu (Food Bioscience, 2026)

Photothermal-amplified single-atom platinum nanozymes on black phosphorus for deep antibacterial therapy - Bairui Zeng; Dongyang Zheng; Anni Wu; Yanjing Zhang; Peng Ding; Zhixiang Mu; Junhao Xiang; Shuangshuang Xu; Xiaoliang Qi; Jianliang Shen; Zhennan Deng (Chemical Engineering Journal, 2026)

A multi-source precipitation blending method combining hydrological model-guided precipitation adjustment and double transfer learning-based data merging - Jingyang Wang; Xiang Li; Ruiyan Wu; Xiangpeng Mu; Jiahua Wei; Yuefei Huang; Shenglong Gu; Dongqin Yin; Xin Tao; Keyan Xu (Journal of Hydrology, 2026)

A modified SLD-ESD model for characterizing and predicting supercritical CH4 adsorption on shale at wide temperatures and pressures - Ke Hu; Chunkui Mu; Zhaolong Ge; Xiang Ao (Fuel, 2026)

The transformation of Ca/Mg-silicate to Co/Ni/Fe-silicate in biomass carbon from gourd leaves for supercapacitors - Shaoqing Zhang; Xiang Ke; Tianming Lv; Jiqi Zheng; Yang Mu; Xuchun Wang; Miao Cui; Teng Du; Changgong Meng (Chemical Engineering Journal, 2026)

Genome-wide association analysis and candidate gene identification for plant height in Shanxi local foxtail millet varieties - Wei Zhou; Huibin Qin; Haigang Wang; Hui Zhi; Rui Huang; Sen Hou; Junjie Wang; Ling Chen; Xiang Tian; Zhijun Qiao; Zhixin Mu; Xianmin Diao (Theoretical and Applied Genetics, 2026)

Intraguild predation risks revealed by functional responses: laboratory evaluation of three spider species preying on the generalist predatory Arma custos (Hemiptera: Pentatomidae) - Yin-Lin Mu; Jun-Yi Gao; Lin Yang; Mao-Xian Wang; Xiang-Sheng Chen (Phytoparasitica, 2026)

Spatiotemporal patterns of bacterial communities and their responses to environmental gradients in a river–reservoir system - Yuhai Zhuo; Nan Li; Bobo Liu; Jianwu Li; Anli Song; Hao Mu; Fei Zhang; Xiang Liu; Zhi Yang; Tinglin Huang; Hongxi Zheng (Antonie van Leeuwenhoek, 2026)

Evaluating the correction methods for NDVI angular effect based on decametric resolution BRDF observations over cropland - Yuhan Guo; Xihan Mu; Xiang Lyu; Dasheng Fan; Chengzhuo Lei; Donghui Xie; Guangjian Yan (Remote Sensing of Environment, 2026)

Predictive Multi-Physics coupling coal combustion model under rapid heating - Hanjian Li; Ying Zhao; Shichen Ding; Xiaoxuan Lyu; Yi Wang; Sheng Su; Song Hu; Jun Xiang; Qingsong Mu; Yanfei Li; Xian Fan; Huanying Chi (Fuel, 2026)

Mixing and stratification dynamics shape bacterial community composition, assembly patterns, and co-occurrence networks in Han River cascade reservoirs - Hao Mu; Haihan Zhang; Jianwu Li; Anli Song; Bobo Liu; Yuhai Zhuo; Fei Zhang; Xiang Liu; Tinglin Huang; Nan Li; Hongxi Zheng (Environmental Research, 2026)

Nb5+ pre-intercalation synergistically regulates layered vanadates for high-performance aqueous Zn-ion batteries - Shenglin Zhong; Denglian Chen; Xiang Hu; Han Lin; Menghui Mu; Zhenhai Wen; Jiangcong Zhou (Chemical Engineering Journal, 2026)

Roles of ACSL6 in lipid homeostasis and stress responses in the nervous system - Shaoyang Zhang; Fangyu Meng; Yuhang Yuan; Hongyu Xiong; Faqin Mu; Xiang Li; Lingqiao Wu; Xiaopeng Yang; Xingyu Li; Yizhe Mu; Ceshi Chen; Huixin Wu; et al. (Metabolic Brain Disease, 2026)

A smartphone-controlled microfluidic platform for rapid, sample-to-answer HLA-B*58:01 genotyping via LNA-enhanced duplex RPA - Xinpei Pang; Zhubing Lei; Xiang Mu; Shuang Wu; Wen-Fei Dong; Qian Mei (Chemical Engineering Journal, 2026)

Interactions between nocturnal ozone enhancement and daytime ozone pollution in Guangxi, South China - Yijun Mu; Shanshan Wang; Sanbao Zhang; Jingying Mao; Ruibin Xue; Chuanqi Gu; Jiaqi Liu; Shuyao Xiang; Bin Zhou (Journal of Environmental Sciences, 2026)

A novel antioxidant peptide DD12 (DWPDARGIWHND) derived from dry cured ham alleviates H2O2-induced oxidative damage via the Keap1-Nrf2-ARE pathway - Ying-dao Nan; Si-qi Chen; Guan-hao Li; Ting-yu Li; Bai-de Mu; Juan Wang; Jian Feng; Hong-mei Li; Chun-xiang Piao (Food Research International, 2026)

Layered nitrogen application drives changes in nitrogen nutrition status of wheat by affecting key soil microbial clusters - Yang Zhou; Pengjia Wu; Yanjie Qu; Shengyan Pang; Haimeng Mu; Min Yang; Xiang Lin; Dong Wang (European Journal of Agronomy, 2026)

Distinct and interactive effects of multiple consumers on plant trade‐offs and diversity in alpine meadows - Yimin Zhao; Peng Zhang; Junsheng Ke; Yilin Dang; Kui Hu; Zijian Yu; Hongying Jiang; Chenrui Wang; Wenjie Li; Jing Zhang; Dong Zhang; Xue Zhang; et al. (Ecology, 2026)
Plants face a fundamental trade‐off between acquiring resources for growth or interspecific competition and simultaneously investing in anti‐consumer defenses. These selective pressures shape species' life history strategies and promote stable coexistence. However, the specific roles of distinct consumer groups, particularly the often‐overlooked oomycetes, in driving growth–defense trade‐offs and sustaining plant diversity remain poorly understood. To this end, we conducted a factorial field experiment in an alpine meadow on the Qinghai‐Tibetan Plateau, manipulating the nitrogen supply (to test resource acquisition effects) and removing consumer groups (i.e., mammalian herbivores, fungi, and oomycetes) both individually and in combination. We used standardized major axis regression to investigate how plant species differentially allocate resources between growth, competition, and defense, and how such trade‐offs influence plant species diversity. Species' responses to nitrogen addition and consumer removal were positively correlated, supporting the existence of widespread growth–defense trade‐offs. The strength of this trade‐off varied significantly among consumer removal treatments, with fungi and herbivores exerting stronger effects than oomycetes. The removal of both herbivores and oomycetes amplified their individual impacts on plant growth–defense trade‐offs. Consistent with this pattern, the removal of fungi or herbivores, but not oomycetes, led to pronounced declines in plant diversity. Our findings reveal the divergent roles of individual consumer groups in shaping plant life history strategies and highlight that cross‐trophic interactions, particularly those involving herbivores or fungal pathogens, are critical for maintaining plant diversity.

Finite-time adaptive event-triggered control for USV trajectory tracking combined with intrinsic curiosity sequential proximal policy optimization - Xiaoning Zhang; Yunsheng Fan; Shengli Dong; Zhipeng Shen; Dongdong Mu; Xiang Ye; Peng Liu (Ocean Engineering, 2026)

Effect of CO2 and H2O on pyrolysis characteristics and structural evolution of Zhundong coal under rapid heating rate - Huanying Chi; Shichen Ding; Ying Zhao; Xiaoxuan Lyu; Yi Wang; Sheng Su; Song Hu; Jun Xiang; Qingsong Mu; Yanfei Li; Xian Fan; Hanjian Li (Fuel, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Fe3O4 nanoparticles and cytochrome c synergistically facilitate lactate chain elongation to caproate - Yichao Wang; Chunhui Zhao; Fangyuan Feng; Yaomin Xi; Wenhan Chen; Xiaoyu Zhu; Xiang Li; Chuanshun Zhi; Hui Mu (Journal of Environmental Chemical Engineering, 2026)

Satellite-observed significant decrease in Arctic phytoplankton biomass during the COVID-19 pandemic due to reduced land-based nutrient inputs - Tianyi Hao; Chao Liu; Huan Hu; Jinzhao Xiang; Bing Mu; Tingwei Cui (Water Research, 2026)

Rice SINA E3 ligases dichotomously control ERECTA1 ubiquitination and stability to regulate panicle morphogenesis and grain yield - Zi-Qi Lu; Tao Guo; Ying-Jie Cao; Jun-Xiang Shan; Wang-Wei Ye; Nai-Qian Dong; Yi Kan; Yi-Bing Yang; Shuang-Qin Guo; Jie-Jie Lei; Xiao-Rui Mu; Ji-Fu Zhou; et al. (Molecular Plant, 2026)

Highly efficient Xe/Kr separation within a metal-organic framework featuring continuous molecule traps - Yan-Long Zhao; Xiang-Yu Li; Xuefeng Bai; Mu-Zi Li; Xin Zhang (Chemical Engineering Journal, 2026)

Design of Sn-doped MoS2 piezocatalyst for high-efficiency antibiotic degradation: mechanism and performance - Mingyang Xu; Xiang Wang; Jingyu Yu; Zhenlin Mu; Shengjun Yang; Chenxi Guo; Guoxuan Li; Yinglong Wang; Fanqing Meng (ENGINEERING Environment, 2026)

A hybrid model driven by remotely-sensed data for simulating the impact of high spatiotemporal variations in fertilization and atmospheric N2O on N2O emissions in paddy fields - Wei Jiang; Xiang Gao; Housheng Wang; Xuerong Lang; Shuai Shen; Xian Hu; Linkai Wen; Qinchun Xu; Yan zhang; Xiaosan Jiang; Jinyang Wang; Yanfeng Ding; et al. (Agricultural and Forest Meteorology, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Directional and adaptive forgetting factor based recursive least square algorithms for maneuvering dynamic identification and motion prediction of unmanned surface vessel - Mu Tan; Gong Xiang; Xianbo Xiang; Shuhang Yu; Kunpeng Rao; Carlos Guedes Soares (Ocean Engineering, 2025)

PMTFIM: Integrating machine learning with nutrient balance theory to estimate multi-stage paddy fertilization information at field scale over large regions - Housheng Wang; Xiang Gao; Wei Jiang; Xuerong Lang; Xian Hu; Meihua Qiu; Qiankun Guo; Yonghong Liang; Xuelei Wang; Yue Mu; Rui Ren; Ganghua Li; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

MicroRNA-451: A multifaceted regulator in cerebral and cardiac ischemia-reperfusion injury - from molecular mechanisms to therapeutic potential - Fei-xiang Wang; Zu-an Shi; Zi-hang Yu; Bin Lu; Guo Mu (Molecular Biology Reports, 2025)

A hybrid model based on machine learning and improved Jayaweera-Mikkelsen model to simulate NH3 volatilization in paddy field water - Xuerong Lang; Xiang Gao; Housheng Wang; Wei Jiang; Shuai Shen; Xian Hu; Linkai Wen; Qinchun Xu; Yan Zhang; Jinyang Wang; Yanfeng Ding; Yue Mu; et al. (Agricultural and Forest Meteorology, 2025)

Revolutionizing toxicological risk assessment: integrative advances in new approach methodologies (NAMs) and precision toxicology - Qiu-Shuang Sheng; Bin Liu; Xiao Wang; Lei Hua; Shou-Cheng Zhao; Xiao-Zhong Sun; Mu-Yang Li; Xiang-Yu Zhang; Jia-Xu Wang; Pei-Li Hu (Archives of Toxicology, 2025)

Built environment impacts on zonal shared e-scooter expenses: A Bayesian learning approach - Guocong Zhai; Ruigan Wang; Xiang Liu; Miloš N. Mladenović; Yandong Tang; Huaqiao Mu; Xiaobo Liu; Hongtai Yang (Transportation Research Part D: Transport and Environment, 2025)

Towards sustainable separation of fuel additives - containing azeotrope by energy-saving extractive distillation process - Xiang Wang; Zhifan Chen; Jingyu Yu; Zhenlin Mu; Ying Xu; Yinglong Wang; Zhaoyou Zhu; Peizhe Cui; Guoxuan Li (Process Safety and Environmental Protection, 2025)

Dysfunction of cerebrospinal fluid circulation and neurovascular decoupling in end-stage renal disease patients with mild cognitive impairment - Zhaoyao Luo; Lurui Bo; Xinyi Zhu; Qiange Zhu; Huijie Yuan; Wen Gu; Peng Li; Yihao Peng; Xiang Chen; Ming Zhang; Shaohui Ma; Junya Mu (GeroScience, 2025)
End-stage renal disease (ESRD) patients frequently experience mild cognitive impairment (MCI), which significantly affects their quality of life. Although dysfunctions in cerebrospinal fluid (CSF) circulation and neurovascular coupling (NVC) have been implicated in cognitive impairment, their interrelationship remains unclear. This study aimed to investigate the association between CSF circulation dysfunction and NVC disruption in ESRD patients with MCI. We enrolled 68 ESRD patients with MCI and 65 healthy controls (HCs). CSF circulation was assessed using choroid plexus volume (CPV), the diffusion tensor imaging along the perivascular space (DTI-ALPS) index, and perivascular space volume fraction (PVSVF). NVC was evaluated using coupling metrics between cerebral blood flow (CBF) and resting-state functional magnetic resonance imaging (MRI) indicators: amplitude of low-frequency fluctuation (ALFF), fractional ALFF (fALFF), and regional homogeneity (ReHo). Cognitive performance was measured using a battery of neuropsychological tests. Compared to HCs, ESRD patients showed significantly increased CPV ( P < 0.001) and enlarged PVSVF ( P < 0.05), along with a decreased DTI-ALPS index ( P < 0.01). Global and regional NVC metrics were significantly reduced in ESRD patients ( P < 0.001). Moreover, regional NVC metrics were negatively correlated with CPV. Mediation analysis further revealed that CBF-ReHo coupling in the left cingulate gyrus pregenual area 32 mediated the relationship between elevated LCPV and cognitive decline. These findings suggest that CSF circulation dysfunction and impaired NVC are interrelated in ESRD-MCI. Disruption of CSF circulation may contribute to cognitive decline by impairing NVC, highlighting both as potential targets for early diagnosis and intervention in ESRD-related cognitive impairment.

Dual-functionalized MIL-53-NH₂ MOFs for high-capacity and reversible ammonia storage: Synergistic effects of hydrogen bonding and electrostatic interactions - Lei Zhang; Guifeng Xiang; Lei Zhang; Ruikang Song; Ying Wang; Yidan Mu; Ziqing Liu (Journal of Environmental Chemical Engineering, 2025)

Multi-constraint analysis reveals distinct aerosol effects on high cloud properties at SACOL and SGP sites - Yang Xia; Jinming Ge; Qingyu Mu; Yue Hu; Nan Peng; Ziyang Qin; Xiang Li; Chi Zhang; Bochun Liu (Atmospheric Research, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

A runoff prediction approach based on machine learning, ensemble forecasting and error correction: A case study of source area of Yellow River - Jingyang Wang; Xiang Li; Ruiyan Wu; Xiangpeng Mu; Baiyinbaoligao; Jiahua Wei; Jie Gao; Dongqin Yin; Xin Tao; Keyan Xu (Journal of Hydrology, 2025)

Dysregulated homocysteine metabolism and cardiovascular disease and clinical treatments - Xiangyu Cao; Tingyu Wang; Gaohang Mu; Yupeng Chen; Bo Xiang; Jingze Zhu; Zhenya Shen (Molecular and Cellular Biochemistry, 2025)

A high accuracy, spatiotemporal coverage, and resolution satellite dataset of water clarity and Forel-Ule Index over China coastal waters (2003–2023) - Tianyi Hao; Binyu Wang; Xuyan Li; Jinzhao Xiang; Bing Mu; Tingwei Cui (Acta Oceanologica Sinica, 2025)

Soil Microbiota From Warmer and Drier Grasslands Are More Vulnerable to Drought Stress - Xihang Yang; Yong Zhang; Xinyue Zhang; Yuting Wang; Xiang Liu; Mu Liu; Yao Xiao; Jihua Wu (Global Change Biology, 2025)
The stability of soil microbial communities under drought stress is critical for sustaining ecosystem function in a changing climate. However, it remains unclear whether long‐term exposure to arid environments strengthens microbial drought resistance through adaptation, or instead diminishes it by reducing diversity and shifting functional redundancy. To address this, we sampled soil microbiota (including bacteria, fungi, and protists) communities along a 3600‐km aridity and temperature gradient in Chinese grasslands, and assessed their compositional resistance to experimental drought. We found that microbiota drought resistance decreased with increasing aridity and temperature, particularly for bacteria and protists. This reduced resistance was attributed to declines in taxonomic diversity, larger microbiota body size, and compositional shifts toward oligotrophic taxa in drier regions. These findings suggest that structural shifts in soil communities associated with chronic arid climate may heighten vulnerability to acute drought events, potentially eroding ecosystem resistance as future climate extremes intensify.

Beyond Paradox: Ozone Therapy as a Hormetic Modulator in Ischemia-Reperfusion Injury - An Update - Yong Ye; Zi-hang Yu; Liang Nie; Fei-xiang Wang; Guo Mu (Cell Biochemistry and Biophysics, 2025)

Mechanism study of enhanced gas recovery and CO2 storage in naturally fractured carbonate reservoirs using a dual-permeability model coupled with association equation of state - Wei Xiong; Yu-Long Zhao; Lie-Hui Zhang; Shao-Mu Wen; Li-Li Liu; Zheng-Lin Cao; Cheng Cao; Xiang-Yu Liu; Xian-Yu Jiang (Gas Science and Engineering, 2025)

Development of cell labeling and gene editing tools in urochordate Ciona - Xiang Li; Lu Mu; Hongzhe Peng; Sun Nyunt Wai; Longjun Pu; Bo Dong (Marine Life Science & Technology, 2025)
Urochordate Ciona spp. are ideal marine model organisms for studying embryogenesis and developmental and evolutionary biology. However, the effective implementation of genetic labeling and CRISPR/Cas9-based editing tools at cellular resolution remains challenging. This study successfully developed and validated a collection of Gateway-based vectors for cell labeling in Ciona spp. The destination vector sets contained two Gateway cassettes flanked by Minos sites, allowing the N- or C-terminal tagging of a protein of interest with various fluorescent markers. In addition, we optimized the CRISPR/Cas9 and CRISPR/dCas9 systems by incorporating P2A-mCherry, a fluorescent indicator for Cas9 expression at cellular resolution. We demonstrated the effective destruction or inhibition of target genes when CRISPR constructs were introduced into fertilized eggs. Furthermore, we engineered a dual fluorescence sensor system that helps visualize successful gene knockouts at the cellular level in specific tissues. The genetic tools developed in this study offer a robust method for gene expression, cell tracking, and subcellular protein localization while also facilitating tissue-specific functional analysis in Ciona embryos and other model systems.

Enhancing regional-scale simulation accuracy of paddy runoff by coupling water balance models with remote sensing - Housheng Wang; Rui Ren; Xiang Gao; Huazhan Zhang; Wei Jiang; Xuerong Lang; Xian Hu; Xiaosan Jiang; Kun Zhao; Bin Zhang; Zhipeng Liu; Wenjuan Zheng; et al. (Journal of Hydrology, 2025)

Development of cascade nanoreactors by fusing bone-targeting engineered extracellular vesicles to modulate bone microenvironment for treatment of diabetic osteoporosis - He Yi; Fang Depeng; Chen Xiang; Shen Hongdou; Shao Xiaoyan; Lin Jiaquan; Liu Na; Shen Tao; Wang Chengzhi; Zhang Pan; Peng Rui; Mu Jinglan; et al. (Chemical Engineering Journal, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Dissolved organic matter mitigates the toxicity of silver nanoparticles to freshwater algae: Effects on oxidative stress and membrane function - Jilai Zhang; Chenglei Hu; Ming Jiang; Qianqian Xiang; Sheng Wang; Youbo Su; Naiming Zhang; Zhihao Si; Yuning Mu; Ran Yang (Environmental Pollution, 2025)

Oral delivery of probiotic combined natural phenolic-metal framework with microencapsulation for prolonged intestinal retention and alleviation of inflammatory bowel disease - Mengna Zhao; Longkai Mu; Fangqin Xiang; Wenqing Lv; Haixin Jiang; Guanyu Tao; Bailiang Li (Chemical Engineering Journal, 2025)

Fabrication of a high strength, swelling resistance, and conductive hydrogel for flexible underwater sensor via ketalization - Kejun Zhong; Jie Xiang; Yu Liu; Chuanlin Song; Yuetong Mu; Ting Yao; Kai Zhao; Tianfeng Gu; Pengxiang Jia; Wenyan Zhang (Chemical Engineering Journal, 2025)

Deep learning-driven reconstruction of PM2.5 vertical profiles: A fusion of lidar and tower data - Zihuai Yi; Yan Xiang; Long Yun; Xi Mu; Zhenyi Chen; Yuanzhu Dong; Feilong Li; Yin Pan; Lihui Lv; Tianshu Zhang; Wenqing Liu (Journal of Cleaner Production, 2025)

Hypogene sulfide precipitation during phyllic alteration: insights from copper isotopic evolution of the Dexing porphyry Cu–Mo–Au deposit, South China - Jia-Feng He; Guo-Guang Wang; Matthew J. Brzozowski; Pei Ni; Xiang-Long Luo; Jun Mu; Weiqiang Li (Mineralium Deposita, 2025)

Temperature and microbial metabolic limitations govern microbial carbon use efficiency in the Tibetan alpine grassland - Xuejun He; Fangbin Liu; Tian Ma; Ase Ma; Yaoyao Wang; Yifan Li; Wenjing Gao; Zhiying Yang; Junsheng Ke; Yao Xiao; Li Zhang; Mu Liu; et al. (Applied Soil Ecology, 2025)

Synchronous monitoring agricultural water qualities and greenhouse gas emissions based on low-cost Internet of Things and intelligent algorithms - Huazhan Zhang; Rui Ren; Xiang Gao; Housheng Wang; Wei Jiang; Xiaosan Jiang; Zhaofu Li; Jianjun Pan; Jinyang Wang; Songhan Wang; Yanfeng Ding; Yue Mu; et al. (Water Research, 2025)

Diatom assemblages indicated ecological shifts over the past two centuries in Bosten Lake, northwest China: Natural and anthropogenic forcings - Muhammad Farqan; Lixiong Xiang; Lan Jiang; Wenjia Wang; Min Zheng; Xiaoyan Mu; Xin Liu; Xueqing Song; Zezhou Zhu; Ramamoorthy Ayyamperumal; Xiaozhong Huang (Quaternary International, 2025)

A meta-analysis of influencing factors on soil pollution around copper smelting sites - Mu Li; Xue Li; William Hartley; Xinghua Luo; Chao Xiang; Jie Liu; Junkang Guo; Shengguo Xue (Journal of Environmental Management, 2024)

Association between angiotensin-converting enzyme gene insertion/deletion polymorphism and cognition impairment in patients with schizophrenia - Li Mu; Dongmei Wang; Meihong Xiu; Xiang-Yang Zhang (Psychopharmacology, 2024)

Western Mongolian Plateau exhibits increasing Holocene temperature - Chong Huang; Xiaozhong Huang; Jinbao Li; Ling Wang; Lan Jiang; Lixiong Xiang; Jun Zhang; Yu Hu; Xiaoyan Mu; Min Zheng; Xiuxiu Ren; Tao Wang; et al. (Global and Planetary Change, 2024)

From flavor to function: A review of fermented fruit drinks, their microbial profiles and health benefits - Yu-Han Yuan; Dong-Dong Mu; Li Guo; Xue-Feng Wu; Xiang-Song Chen; Xing-Jiang Li (Food Research International, 2024)

Smart nanoscale lamellated supramolecular assemblies overcome biofilm barriers and enhance foliar affinity for efficient control of bacterial diseases - Lizhu Xiang; Xiaohui Wang; Jinghan Yang; Rui Wang; Lin Chen; Xiaoping Bao; Xianfu Mu; Peiyi Wang (Chemical Engineering Journal, 2024)

The mechanism of MMP14-positive tumor-associated fibroblast subsets in inhibiting PD-1 immunotherapy for esophageal cancer through exosomal tsRNA-10522 - Juzheng Wang; Chunlong Zheng; Jiayu Lu; Xinyao Xu; Guangyu Xiang; Jiahe Li; Jipeng Zhang; Xiaorong Mu; Qiang Lu (Functional & Integrative Genomics, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Tin isotope heterogeneity and baseline of the upper continental crust - Jia-Xin She; Weiqiang Li; Edith Kubik; Frédéric Moynier; Xiang-Long Luo; Jun Mu; Shichao An; Chang-Zhi Wu; Zhongya Hu; Junfeng Ji (Geochimica et Cosmochimica Acta, 2024)

Anthropogenic forest degradation and its impact on soil erosion in the mountainous region of northern China - Xiuxiu Ren; Chong Huang; Zezhou Zhu; Ling Wang; Ning Wang; Xiaoyan Mu; Derui Luo; Jun Zhang; Lixiong Xiang; Xiaozhong Huang (CATENA, 2024)

Exploring the novel antioxidant peptides in low-salt dry-cured ham: Preparation, purification, identification and molecular docking - Ying-dao Nan; Bai-de Mu; Chang-xin Ge; Si-qi Chen; Ming-xun Cui; Hong-mei Li; Chang-cheng Zhao; Juan Wang; Chun-xiang Piao; Guan-hao Li (Food Chemistry, 2024)

sp2-c linked Cu-based metal-covalent organic framework for chemical and photocatalysis synergistic reduction of uranium - Jin-Lan Liu; Mu-Xiang Lin; Juan Huang; Cheng-Rong Zhang; Jia-Xin Qi; Yuan-Jun Cai; Xiao-Juan Chen; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

High-density mapping of durable and broad-spectrum stripe rust resistance gene Yr30 in wheat - Xiaoting Wang; Mingjie Xiang; Huaizhou Li; Xiaoxiao Li; Keqing Mu; Shuo Huang; Yibo Zhang; Xiangrui Cheng; Shuqing Yang; Xunying Yuan; Ravi P. Singh; Sridhar Bhavani; et al. (Theoretical and Applied Genetics, 2024)

Delivery of neurotrophin-3 by RVG-Lamp2b-modified mesenchymal stem cell-derived exosomes alleviates facial nerve injury - Wenting Bi; Xiaodan Mu; Yongfeng Li; Qingyan Sun; Lei Xiang; Min Hu; Huawei Liu (Human Cell, 2024)

Variation of enzymes activities in haemocytes and serum of honeysuckle geometrid, Heterolocha jinyinhuaphaga Chu (Lepidoptera: Geometridae) larvae infected by Escherichia coli - Yu-yong Xiang; Xiu-jie Mu; Yan Zhao (International Journal of Tropical Insect Science, 2024)

Milk fat globule membrane regulates the physicochemical properties and surface composition of infant formula powders by improving the stability of the emulsion - Bailiang Li; Qingxue Chen; Longkai Mu; Sibo Liu; Fangqin Xiang; Liu Yang; Sufang Duan; Fang Li; Ignatius Man-Yau Szeto (Food Chemistry, 2024)

Efficient trimethoprim removal via cooperation of radical and non-radical pathways in UV/peroxymonosulfate: Kinetics, mechanisms and disinfection by-products-associated risks - Chen-Cheng Mo; Fu-Xiang Tian; Bin Xu; Juan Wang; Yu-Qiong Gao; Dong-Su Bi; Bo Wang; Xing-Yan Mu; Xiao-Jun Hu (Journal of Environmental Chemical Engineering, 2024)

Linking carbon cycle perturbations to the Late Ordovician glaciation and mass extinction: A modeling approach - Junpeng Zhang; Chao Li; Yangyang Zhong; Xuejin Wu; Xiang Fang; Mu Liu; Daizhao Chen; Benjamin C. Gill; Thomas J. Algeo; Timothy W. Lyons; Yuandong Zhang; Hui Tian (Earth and Planetary Science Letters, 2024)

Glyphosate exposure affected longevity-related pathways and reduced survival in asian honey bees (Apis cerana) - Dong Zhi-Xiang; Li Wan-Li; LI Xi-Jie; Li Jia-Li; Zhang Jun; Zhao Chong-Hui; Huang Qi; Cao Zhe; Chen Yuan; Zhao Hong-Mu; Guo Jun; Tian Wen-Li (Chemosphere, 2024)

First Pediastrum–temperature transfer function and its application to mid-to-late Holocene reconstruction in Central Asia - Lixiong Xiang; Xiaozhong Huang; Jiawu Zhang; Chong Huang; Antje Schwalb; Jifeng Zhang; Natalia Rudaya; Mingjie Sun; Xiaoyan Mu; Yuan Li; Derui Luo; Farqan Muhammad; et al. (Quaternary Science Reviews, 2024)

Depositional and diagenetic controls on hydrocarbon generation of mudstones through clay–organic matter interactions: A comparative study of the Dongpu Depression, Bohai Bay Basin, China - Jiazong Du; Jingong Cai; Xiang Zeng; Yunxian Zhang; Xiaoshui Mu; Xinyu Wang (Journal of Asian Earth Sciences, 2024)

Genomic features of a plant growth-promoting endophytic Enterobacter cancerogenus JY65 dominant in microbiota of halophyte Suaeda salsa - Mu Peng; Zhihui Jiang; Zhiwen Xiang; Aifen Zhou; Chao Wang; Zhiyong Wang; Fangzhen Zhou (Plant and Soil, 2024)

Capturing spatiotemporal heterogeneity in fertilizer application for better modelling paddy water nitrogen and phosphorus pollution at regional scale - Rui Ren; Huazhan Zhang; Xiang Gao; Housheng Wang; Wei Jiang; Yuhui Wang; Xiaosan Jiang; Zhaofu Li; Haiyan Zhao; Ganghua Li; Yanfeng Ding; Yue Mu (Agriculture, Ecosystems & Environment, 2024)

Contrasting roles of fungal and oomycete pathogens in mediating nitrogen addition and winter grazing effects on biomass - Peng Zhang; Mengjiao Huang; Chaorui Chen; Kui Hu; Junsheng Ke; Mu Liu; Yao Xiao; Xiang Liu (Ecology, 2024)
Both bottom‐up and top‐down processes modulate plant communities. Fungal and oomycete pathogens are most common in global grasslands, and due to differences in their physiology, function, host range, and life cycles, they may differentially affect plants (in both intensity and direction). However, how fungal and oomycete pathogens regulate bottom‐up and top‐down effects on plant community biomass remains unclear. To this end, we conducted a 3‐year field experiment in an alpine meadow incorporating mammalian herbivore exclosure, fungicide/oomyceticide application, and nitrogen addition treatments. We arranged 12 blocks with half randomly assigned to be mammalian herbivore exclosures (fenced to exclude grazing sheep), and the other half were fenced most of the year but not in winter (winter grazing control). Six 2.5 × 2.5 m square plots were established in each block, with each of the six plots assigned as control, nitrogen addition, fungicide application, oomyceticide application, nitrogen addition + fungicide application, and nitrogen addition + oomyceticide application. We found that fungicide application significantly increased plant community biomass (mainly Poaceae species) under nitrogen addition and promoted the bottom‐up effect of nitrogen addition on plant community biomass by altering the community‐weighted mean of plant height (via species turnover). Meanwhile, oomyceticide application significantly increased plant community biomass (mainly Poaceae species) when mammalian herbivores were excluded and weakened the top‐down effect of winter grazing on plant community biomass by driving intraspecific variation in plant height. Our results highlight that fungal and oomycete pathogens play important (but differing) roles in mediating the effects of nutrient availability and higher trophic levels on plant community biomass. Mechanistically, we demonstrated that plant pathogen‐related modulation of plant community biomass is achieved by alterations to plant height. Overall, this study combines both community and disease ecology to reveal complex interactions among higher trophic levels and their potential impacts on terrestrial ecosystem functioning under human disturbance.

Epidural administration of large dose of opioid μ receptor agonist may impair cardiac functions and myocardial viability via desensitizing transient receptor potential vanilloid 1 - Xiang Ma; Zheng Guo; Mu-Rong Li; Lu Chen; Xing Zhao; Tian-Qi Wang; Tao Sun (Toxicology and Applied Pharmacology, 2024)

Occurrence, distribution, potential sources, and risks of organophosphate esters in fresh snow on Urumqi Glacier No. 1, eastern Tien Shan, China - Yishen Wang; Yuxin Ma; Jinghua Zhang; Zhongqin Li; Feiteng Wang; Shuang-ye Wu; Jianxin Mu; Xiang Zou; Jianjie Liu; Zhaojun Zhan; Shugui Hou (Science of The Total Environment, 2024)

Construction of and evaluation of the immune response to two recombinant pseudorabies viruses expressing the B119L and EP364R proteins of African swine fever virus - Xin-Mei Geng; Ying-Mu Xi; Xiang-Mei Huang; Yang-Lin Wang; Xu-Ying Wang; Kang Ouyang; Ying Chen; Zu-Zhang Wei; Yi-Feng Qin; Wei-Jian Huang (Archives of Virology, 2024)

Satellite-observed significant improvement in nearshore transparency of the Bohai Sea during pollution control - Xuyan Li; Jinzhao Xiang; Liudi Zhu; Zhibin Yang; Ting Wei; Bing Mu; Xiaobo Zhang; Tingwei Cui (Acta Oceanologica Sinica, 2023)

Geochronology and in-situ apatite geochemistry of late Paleoproterozoic A-type granites in the Jiao-Liao-Ji Belt, North China Craton: Implications for petrogenesis and tectonic evolution - Yi-Kang Quan; Mao-Song Mu; De-Bin Yang; Xiang-Yu Yan; An-Qi Wang; Le-Ran Hao; Feng Wang (Geochemistry, 2023)

The regulative effect and repercussion of probiotics and prebiotics on osteoporosis: involvement of brain-gut-bone axis - Yuan-Wei Zhang; Mu-Min Cao; Ying-Juan Li; Guang-Chun Dai; Pan-Pan Lu; Ming Zhang; Li-Yong Bai; Xiang-Xu Chen; Cheng Zhang; Liu Shi; Yun-Feng Rui (Critical Reviews in Food Science and Nutrition, 2023)

Refining health risk assessment of arsenic in wild edible boletus from typical high geochemical background areas: The role of As species, bioavailability, and enterotoxicity - Mengying Li; Zheng Chen; Qing Xiong; Yunzhen Mu; Yumei Xie; Mengyan Zhang; Lena Q. Ma; Ping Xiang (Environmental Pollution, 2023)

Lactate Improves Long-term Cognitive Impairment Induced By Repeated Neonatal Sevoflurane Exposures Through SIRT1-mediated Regulation of Adult Hippocampal Neurogenesis and Synaptic Plasticity in Male Mice - Li-Li Qiu; Xiao-Xiang Tan; Jiao-Jiao Yang; Mu-Huo Ji; Hui Zhang; Chunjie Zhao; Jiang-Yan Xia; Jie Sun (Molecular Neurobiology, 2023)

Evaluating the effectiveness of coastal environmental management policies in China: The case of Bohai Sea - Jinzhao Xiang; Tingwei Cui; Xuyan Li; Qian Zhang; Bing Mu; Rongjie Liu; Wenjing Zhao (Journal of Environmental Management, 2023)

Geographical variation in community‐wide herbivory matches patterns of intraspecific variation instead of species turnover - Xiang Liu; Ziyuan Lin; Kui Hu; Xingxing Wang; Peng Zhang; Yao Xiao; Li Zhang; Mu Liu (Global Ecology and Biogeography, 2023)
Aim Attempts over the past 30 years to explain geographical variation in the strength of herbivore pressure have given rise to ecological hypotheses like the latitudinal herbivory hypothesis. This hypothesis, however, has rarely been tested using community‐level data. Therefore, the aim of our study was to examine the patterns and potential mechanisms underlying geographical variation in community‐wide herbivory. Location The Qinghai‐Tibetan Plateau. Time Period July 2021. Major Taxa Studied Plants. Methods We selected 43 grassland sites along a 1500‐km latitudinal gradient ( c . 27°N to 39°N) and a 2698‐m elevational gradient (1886–4584 m) on the Qinghai‐Tibetan Plateau. We evaluated geographical patterns in invertebrate herbivory pressure at the population and community levels, while also evaluating the importance of geographical variation in mediating the effects of abiotic and biotic factors on intraspecific variation (through changes in herbivory on component species) and species turnover effects (through changes in plant community composition). Results Community‐wide herbivory decreased with latitude, mirroring intraspecific variation, while species turnover effects did not vary along any tested geographical gradients. Furthermore, we found that geographical variation in community‐wide herbivory was strongly positively correlated with soil nitrogen content. We also found a positive effect of soil nitrogen content on intraspecific variation and a negative effect of plant community biomass on species turnover effects. Main Conclusions The latitudinal gradient in community‐wide herbivory was primarily mediated by intraspecific variation, which was in turn associated with a gradient in soil nitrogen content. Our findings highlight the need for community‐wide assessments of geographical variation in plant–herbivore interactions, decomposing community‐wide herbivory into intraspecific variation and species turnover effects.

Short-term effects of individual exposure to PM2.5 on hospital admissions for myocardial infarction and stroke: a population-based case-crossover study in Guangzhou, China - Jie-Qi Jin; Guo-Zhen Lin; Shuang-Ying Wu; Mu-Rui Zheng; Hui Liu; Xiang-Yi Liu; Min-Qian Yan; Zhao-Yue Chen; Chun-Quan Ou (Environmental Science and Pollution Research, 2023)

Impact of antibiotics on microbial community in aquatic environment and biodegradation mechanism: a review and bibliometric analysis - Xiaoying Mu; Zhihua Huang; Okugbe Ebiotubo Ohore; Jinjin Yang; Kai Peng; Shaokang Li; Xiang Li (Environmental Science and Pollution Research, 2023)

Alleviation of substrate inhibition in an anaerobic ammonia oxidation reactor: Recovery process performance and microbial community - Genwang Chang; Yu Yang; Yifei Yang; Jinjin Yang; Shaokang Li; Xiaoying Mu; Jingwen Luo; Xiang Li (Journal of Water Process Engineering, 2023)

Spatial scale‐dependent dilution effects of biodiversity on plant diseases in grasslands - Xiang Liu; Yao Xiao; Ziyuan Lin; Xingxing Wang; Kui Hu; Mu Liu; Yimin Zhao; Yanwen Qi; Shurong Zhou (Ecology, 2023)
The rapid biodiversity losses of the Anthropocene have motivated ecologists to understand how biodiversity affects infectious diseases. Spatial scale is thought to moderate negative biodiversity–disease relationships (i.e., dilution effects) in zoonotic diseases, whereas evidence from plant communities for an effect of scale remains limited, especially at local scales where the mechanisms (e.g., encounter reduction) underlying dilution effects actually work. Here, we tested how spatial scale affects the direction and magnitude of biodiversity–disease relationships. We utilized a 10‐year‐old nitrogen addition experiment in a Tibetan alpine meadow, with 0, 5, 10, and 15 g/m 2 nitrogen addition treatments. Within the treatment plots, we arranged a total of 216 quadrats (of either 0.125 × 0.125 m, 0.25 × 0.25 m or 0.5 × 0.5 m size) to test how the sample area affects the relationship between plant species richness and foliar fungal disease severity. We found that the dilution effects were stronger in the 0.125 × 0.125 m and 0.25 × 0.25 m quadrats, compared with 0.5 × 0.5 m quadrats. There was a significant interaction between species richness and nitrogen addition in the 0.125 × 0.125 m and 0.25 × 0.25 m quadrats, indicating that a dilution effect was more easily observed under higher levels of nitrogen addition. Based on multigroup structural equation models, we found that even accounting for the direct impact of nitrogen addition (i.e., “nitrogen‐disease hypothesis”), the dilution effect still worked at the 0.125 × 0.125 m scale. Overall, these findings suggest that spatial scale directly determines the occurrence of dilution effects, and can partly explain the observed variation in biodiversity–disease relationships in grasslands. Next‐generation frameworks for predicting infectious diseases under rapid biodiversity loss scenarios need to incorporate spatial information.

Evolution mechanism and deformation stability analysis of rock slope block toppling for early warnings - Jian-qiao Mu; Tian-tao Li; Xiang-jun Pei; Run-qiu Huang; Fu-an Lan; Xue-qing Zou (Natural Hazards, 2022)

Characteristics of timberline and treeline altitudinal distribution in Mt. Namjagbarwa and their geographical interpretation - Hao-xiang Mu; Fang Han; Bai-ping Zhang; Tian Liang; Zhi-yong Wang; Zhe Wang (Journal of Mountain Science, 2022)

Validamycin reduces the transmission of Tomato chlorotic virus by Bemisia tabaci - Yang Mu; Xiaobin Shi; Zhuo Zhang; Zhanhong Zhang; Tianqi Wang; Yanqi Wang; Yan Wei; Xuguo Zhou; Min Xiang; Yong Liu; Deyong Zhang (Journal of Pest Science, 2022)

Stability evaluation for steep bank slope with microseismic monitoring in Three Gorges Reservoir area - Qing-ming Xie; Kui Long; Zi-mu Li; Li-chuan Chen; Hong Liu; Hong Xu; Fei He; Dan Liang; Xue-kun Xiang; Qiang Ma (Journal of Mountain Science, 2022)

Standard- vs. low-dose rivaroxaban in patients with atrial fibrillation: a systematic review and meta-analysis - Guangyan Mu; Hanxu Zhang; Zhiyan Liu; Qiufen Xie; Shuang Zhou; Zining Wang; Zhe Wang; Kun Hu; Jingyi Hou; Nan Zhao; Qian Xiang; Yimin Cui (European Journal of Clinical Pharmacology, 2022)

Cytotoxic benzopyranone and xanthone derivatives from a coral symbiotic fungus Cladosporium halotolerans GXIMD 02502 - Chao-Nan Wang; Hu-Mu Lu; Cheng-Hai Gao; Lang Guo; Zhen-Yu Zhan; Jun-Jian Wang; Yong-Hong Liu; Song-Tao Xiang; Jian Wang; Xiao-Wei Luo (Natural Product Research, 2021)

Altered dynamics of functional connectivity density associated with early and advanced stages of motor training in tennis and table tennis athletes - Qing Gao; Yue Huang; Yu Xiang; Chengbo Yang; Mu Zhang; Jingpu Guo; Hu Wang; Jiali Yu; Qian Cui; Huafu Chen (Brain Imaging and Behavior, 2021)

Correlation between single-nucleotide polymorphisms and statin-induced myopathy: a mixed-effects model meta-analysis - Qian Xiang; Xiao-Dan Zhang; Guang-Yan Mu; Zhe Wang; Zhi-Yan Liu; Qiu-Fen Xie; Kun Hu; Zhuo Zhang; Ling-Yue Ma; Jie Jiang; Yi-Min Cui (European Journal of Clinical Pharmacology, 2021)

Association of FMO3 rs1736557 polymorphism with clopidogrel response in Chinese patients with coronary artery disease - Kong-Xiang Zhu; Pei-Yuan Song; He-Li; Mu-Peng Li; Yin-xiao Du; Qi-lin Ma; Li-Ming Peng; Xiao-Ping Chen (European Journal of Clinical Pharmacology, 2021)

MiR-34a suppresses osteoblast differentiation through glycolysis inhibition by targeting lactate dehydrogenase-A (LDHA) - Mu Hong; Xiao-Bin Zhang; Fei Xiang; Xu Fei; Xue-Lian Ouyang; Xiao-Chun Peng (In Vitro Cellular & Developmental Biology - Animal, 2020)

Performance and Spatial Distribution of Functional Bacteria under Low-Temperature Stress in Biofilm Systems for Polluted Source Water Pretreatment - Guang-feng Yang; Li-juan Feng; Jun Mu; Jing-ya Sun; Liang Zhu; Xiang-yang Xu (International Journal of Environmental Research, 2019)

Long-term observation of cyanobacteria blooms using multi-source satellite images: a case study on a cloudy and rainy lake - Meng Mu; Chuanqing Wu; Yunmei Li; Heng Lyu; Shengzhong Fang; Xiang Yan; Ge Liu; Zhubin Zheng; Chenggong Du; Shun Bi (Environmental Science and Pollution Research, 2019)

Streptomyces lutosisoli sp. nov., a novel actinomycete isolated from muddy soil - Yue Shen; Tianyu Sun; Shanwen Jiang; Shan Mu; Dongmei Li; Xiaowei Guo; Jianli Zhang; Junwei Zhao; Wensheng Xiang (Antonie van Leeuwenhoek, 2018)

Land-use change affects stocks and stoichiometric ratios of soil carbon, nitrogen, and phosphorus in a typical agro-pastoral region of northwest China - Xiang Liu; Lanhai Li; Quan Wang; Shuyong Mu (Journal of Soils and Sediments, 2018)

Nonomuraea rhizosphaerae sp. nov., an actinomycete isolated from the rhizosphere soil of a rubber tree (Hevea brasiliensis Muell. Arg) - Junwei Zhao; Shan Mu; Qiannan Zhao; Shanwen Jiang; Peng Cao; Xiaowei Guo; Xiangjing Wang; Wensheng Xiang (Antonie van Leeuwenhoek, 2018)

Identification and Field Evaluation of the Sex Pheromone of Orthaga achatina (Lepidoptera: Pyralidae) - Qi Yan; Hai-Dong Li; Yan Chen; Zhan-Feng Ye; Xi-Yu You; Jun Zhou; Lan-Fang Mu; Shi-Jing Liu; Xiang-Bo Kong; Sajjad Ali Khuhro; Shuang-Lin Dong (Journal of Chemical Ecology, 2018)

Underestimated effects of sediments on enhanced startup performance of biofilm systems for polluted source water pretreatment - Zheng-hui Lv; Jing Wang; Guang-feng Yang; Li-juan Feng; Jun Mu; Liang Zhu; Xiang-yang Xu (Biodegradation, 2018)

Efficient Using Durian Shell Hydrolysate as Low-Cost Substrate for Bacterial Cellulose Production by Gluconacetobacter xylinus - Mu-Tan Luo; Cheng Zhao; Chao Huang; Xue-Fang Chen; Qian-Lin Huang; Gao-Xiang Qi; Lan-Lan Tian; Lian Xiong; Hai-Long Li; Xin-De Chen (Indian Journal of Microbiology, 2017)

IL-1α-induced microvascular endothelial cells promote neutrophil killing by increasing MMP-9 concentration and lysozyme activity - Xiaoye Liu; Hong Dong; Mingming Wang; Ying Gao; Tao Zhang; Ge Hu; Huiqing Duan; Xiang Mu (Immunologic Research, 2016)

Degradation of p-Nitrophenol in Soil by Dielectric Barrier Discharge Plasma - Rui Li; Yanan Liu; Yu Sun; Wenjuan Zhang; Ruiwen Mu; Xiang Li; Hong Chen; Pin Gao; Gang Xue; Stephanie Ognier (Water, Air, & Soil Pollution, 2015)

Glucocorticoid Receptor β Acts as a Co-activator of T-Cell Factor 4 and Enhances Glioma Cell Proliferation - Qian Wang; Pei-Hua Lu; Zhi-Feng Shi; Yan-Juan Xu; Jie Xiang; Yan-Xia Wang; Ling-Xiao Deng; Ping Xie; Ying Yin; Bin Zhang; Hui-Jun Mu; Wei-Zhen Qiao; et al. (Molecular Neurobiology, 2015)

Management planning for endangered plant species in priority protected areas - Chun-Jing Wang; Ji-Zhong Wan; Xian-Yun Mu; Zhi-Xiang Zhang (Biodiversity and Conservation, 2015)

Whole exome sequencing identifies mutation of EDNRA involved in ACTH-independent macronodular adrenal hyperplasia - Jie Zhu; Liang Cui; Wei Wang; Xing-Yi Hang; A-Xiang Xu; Su-Xia Yang; Jing-Tao Dou; Yi-Ming Mu; Xu Zhang; Jiang-Ping Gao (Familial Cancer, 2013)

Liver proteomic analysis of the large yellow croaker (Pseudosciaena crocea) following polyriboinosinic:polyribocytidylic acid induction - Yinnan Mu; Xiang Wan; Kebing Lin; Jingqun Ao; Xinhua Chen (Fish Physiology and Biochemistry, 2013)

Molecular characterization and expression analysis of GlHMGS, a gene encoding hydroxymethylglutaryl-CoA synthase from Ganoderma lucidum (Ling-zhi) in ganoderic acid biosynthesis pathway - Ang Ren; Xiang Ouyang; Liang Shi; Ai-Liang Jiang; Da-Shuai Mu; Meng-Jiao Li; Qin Han; Ming-Wen Zhao (World Journal of Microbiology and Biotechnology, 2013)

Phylogeny of Celastrus L. (Celastraceae) inferred from two nuclear and three plastid markers - Xian-Yun Mu; Liang-Cheng Zhao; Zhi-Xiang Zhang (Journal of Plant Research, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Expression and characterization of Momordica Chanrantia anti-hyperglycaemic peptide in Escherichia coli - Si-Xiu Liu; Zhong-Ping Fu; Rui-Min Mu; Zhi-Bi Hu; Fu-Jun Wang; Xiang-Rong Wang (Molecular Biology Reports, 2010)

Enhanced migration and CXCR4 over-expression in fibroblasts with telomerase reconstitution - Yi Qu; Meng Mao; Xihong Li; Lin Zhang; Xiang Huang; Chunlei Yang; Fengyang Zhao; Ying Xiong; Dezhi Mu (Molecular and Cellular Biochemistry, 2008)

On the evolution of finite-amplitude disturbance to the barotropic and baroclinic quasigeostrophic flows - Mu Mu; Xiang Jie (Advances in Atmospheric Sciences, 1998)